Modernist Monstrosity in Rimbaud's Verse and Prose Poetry. Issue 2 (July 2018) - Harrow, Susan
Abstract : Rimbaud's poetry and poetics contribute to the prodigious genealogy of monstrosity in Western literature and visual culture. This article argues that monster figures – whether the "familiar" terrors of iconographic tradition, horrible hybrids, or everyday bogeymen – are central to the transformative momentum of modernism in Rimbaud's verse and prose poetry. Monstrosity – multifariously embodied and endlessly morphing – generates social, cultural, and political fantasy, challenging orthodoxies, displacing structures, and empowering readers. Through the lacerating light it projects on forms of cultural constraint and aesthetic (self-) limitation, monstrosity is revealed as the force capable of re-visioning poetry and of deepening our equivocal sense of what it is to be human.